Analisa Kegagalan Material Kepala Silinder Mesin Diesel 4 TAK - Hermawati, Lilin; Mujiarto, Iman; Pratomo, Sunu Arsy; Kundori, Kundori (Jurnal Sains dan Teknologi (JSIT), 2021)
cylinder head is a part that is exposed to thermal and mechanical loads which not only affect engine performance parameters. The purpose of this study is to analyze the failure of the cylinder head structure of a 4 stroke diesel engine and find the cause of the failure. In this study, surveys and measurements of the cylinder head were carried out, to find out the appropriate results so that they could determine cracks, wear, and warping of the cylinder head. The results showed that the maximum bend on the side of the cylinder head attached to the cylinder block was 0.07 mm, 0.08 mm, 0.069mm. While the maximum bending on the side of the cylinder head attached to the manifold is 0.15 mm, 0.14 mm, 0.16 mm. At maximum bending on the side of the cylinder head attached to the exhaust manifold, it is necessary to pay attention to how to use the diesel engine correctly and according to operating hours.